2006
DOI: 10.1111/j.1600-0722.2006.00345.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinpro Cario L‐Pop estimates with CIA lactic acid estimates of the oral microflora

Abstract: Clinpro Cario L-Pop (CCLP) is a semiquantitive test claimed to determine the general potential for caries development and to monitor the individual caries risk. This test translates the capacity of the tongue microflora to produce lactic acid into a score of 1-9, indicating a low, medium or high risk for caries development. The aim of this randomized crossover, clinical trial was to evaluate the CCLP on its variation over time and its capacity to monitor the effect of three different oral hygiene procedures. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The concentration of lactic acid in the tongue coating is known to reach 6.7 to 7.8 mM after a sucrose rinse (26,27) due to the dominance of lactate-producing bacteria such as streptococci (5) and probably results in acidification of the tongue coating. Thus, in the tongue coating, changes in both pH and the lactate concentration may influence H 2 S production by Veillonella.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of lactic acid in the tongue coating is known to reach 6.7 to 7.8 mM after a sucrose rinse (26,27) due to the dominance of lactate-producing bacteria such as streptococci (5) and probably results in acidification of the tongue coating. Thus, in the tongue coating, changes in both pH and the lactate concentration may influence H 2 S production by Veillonella.…”
Section: Discussionmentioning
confidence: 99%
“…Reliability of CCLP was 60% to 80% in a study 13 and only 37% in another. 14 Another study reported that there was no correlation between Streptococcus mutans and Lactobacilli counts in the laboratory by Dentocult and CCLP. 15 On the other hand, Bretz et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results with the use of Clinpro TM Cario L-Pop TM in this study showed an association with high salivary levels of S. mutans. In a clinical trial, Gerardu et al (2006) (17) concluded that Clinpro TM Cario L-Pop TM can be used to monitor and motivate compliance to oral hygiene. In the present study, the results obtained with Clinpro TM Cario L-Pop TM confirmed those obtained with the conventional culture-based method in all cases, showing a perfect agreement.…”
Section: Discussionmentioning
confidence: 99%
“…The reaction is based on the enzymatic degradation of lactic acid by lactate dehydrogenase and coupled to a cascade of redox indicators that generate a color signal, which is analyzed using a semi-quantitative scale. Clinpro TM Cario L-Pop TM has been previously evaluated (16)(17)(18)(19) and, according to Schiffner and Torres-Quintero (16), it can indicate changes in the oral microflora and thus could be used to monitor the effect of interventions.…”
Section: Introductionmentioning
confidence: 99%